Ficus deltoidea leaves extracts - promising therapeutic agent for oral candidiasis and denture stomatitis / Vivi Noryati Ahmad … [ et al.] - Ahmad, Vivi Noryati; Muhammad Zain, Nurhayati; Mohd Amin, Indah; Zulzaidi, Fazleen; Ahmad Jafri, Mimi Syafiqa (2019)
The aims of this study are to investigate antimicrobial and antibiofilm activities of Ficus deltoidea (F. deltoidea) leaves extract against Candida albicans (C. albicans). Methods: The antifungal activity was evaluated using minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). The potential of F. deltoidea leaves extract as antibiofilm agent was evaluated using biofilm inhibition assay and biofilm eradication assay. Chlorhexidine 0.12% (CHX) was used as a positive control. Each experiment was performed in triplicate and repeated four times independently. All the data obtained were analysed using SPSS version 23. Statistical significance measured using Kruskal Wallis test and post-hoc Mann Whitney test which presented as means ±SD with P value <0.001. Results: F. deltoidea extract showed antifungal activity against C. albicans with MIC and MFC, 50mg/ml and 100mg/ml respectively. The extract exhibited inhibitory effect on candida biofilm formation (69.5%). The preformed biofilm was significantly dispersed by extract upon 5 minutes treatment with eradication percentages 66.63%. The biofilm inhibition and biofilm eradication percentages for positive control CHX 0.12% were 43.0% and 58.97% respectively. Conclusion: Results of this study suggest the potential of F. deltoidea leaves extract as preventative and therapeutic agents against candida biofilm-related infections such as oral andidiasis and denture stomatitis.